Phase current control to reduce unbalanced outputs in paralleled inverters - Lee, Bong Ki; Lee, Heon Su; Lee, Kyo Beum (Journal of Power Electronics, 2024)
When paralleled inverters operate an electric motor, a circulating current is typically generated due to a device-switching timing error. To mitigate this error, an AC reactor is installed at the output of the inverters to reduce the circulating current. However, unbalanced output currents (UOCs) are produced due to the difference between the resistance and inductance in the AC reactor. When there is a difference in the output currents of the inverters, a single inverter outputs excessive current. As a result, the motor cannot be controlled to its maximum power. In this study, mathematical modeling is performed and the causes for the generation of UOCs in parallel connected electric motor drive systems are analyzed. Furthermore, the unbalanced load is minimized by controlling the current output based on the output status of the inverters in the control algorithms of a motor. The proposed control method is experimentally verified by implementing a system that connects three inverters in parallel.
Keywords: Circulating current; Motor control; Output current; Paralleled inverters; Paralleled operation; Phase current control; Phase currents; Scalar motor control; Timing errors; Unbalanced output current; Paralleled operation; Phase current control; Scalar motor control; Unbalanced output currents